The Solution:
Given the equation of the hyperbola below:
![(x^2)/(9)-(y^2)/(64)=1](https://img.qammunity.org/2023/formulas/mathematics/college/bhr5nudopwrlgy3sv1u524wxox78f1bpng.png)
We are required to find the equation for the asymptotes of the above hyperbola.
By formula, the equation for the asymptotes is
![\begin{gathered} y=\pm(b)/(a)x \\ \text{Where} \\ a^2=9 \\ a=\pm3 \\ b^2=64 \\ b=\pm8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ub5lxxvm2z4jejd5w3bz0uaiscsst1e9fi.png)
Substituting these values in the formula above, we get
![\begin{gathered} y=\pm(8)/(3)x \\ \text{This becomes} \\ y=+(8)/(3)x\text{ or }y=-_{}(8)/(3)x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5v1zdj7cz5ofd10bh7egi00et8s6kzeb47.png)
Therefore, the correct answer is option D.